2002
DOI: 10.3346/jkms.2002.17.1.41
|View full text |Cite
|
Sign up to set email alerts
|

FKBP-12 Exhibits an Inhibitory Activity on Calcium Oxalate Crystal Growth in Vitro

Abstract: Urolithiasis and calcium oxalate crystal deposition diseases are still significant medical problems. In the course of nephrocalcin cDNA cloning, we have identified FKBP-12 as an inhibitory molecule of calcium oxalate crystal growth. lambdagt 11 cDNA libraries were constructed from renal carcinoma tissues and screened for nephrocalcin cDNA clones using anti-nephrocalcin antibody as a probe. Clones expressing recombinant proteins, which appeared to be antigenically cross-reactive to nephrocalcin, were isolated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Several molecules are known to inhibit CaOx crystal formation in physiologic condition, including nephrocalcin, osteonectin, mannanbinding lectin-associated plasma protein, and FK506-binding protein, some of which are immunolocalized to renal proximal tubules. 8 It is possible that lower levels of these molecules may promote CaOx deposition. Although this hypothesis has not been tested, at least one of these molecules, ie, nephrocalcin, was identified in RCCs and shown to decrease in ESRDassociated RCCs.…”
Section: Discussionmentioning
confidence: 99%
“…Several molecules are known to inhibit CaOx crystal formation in physiologic condition, including nephrocalcin, osteonectin, mannanbinding lectin-associated plasma protein, and FK506-binding protein, some of which are immunolocalized to renal proximal tubules. 8 It is possible that lower levels of these molecules may promote CaOx deposition. Although this hypothesis has not been tested, at least one of these molecules, ie, nephrocalcin, was identified in RCCs and shown to decrease in ESRDassociated RCCs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these stone inhibitors have similar physicochemical properties as they are small anionic proteins that can bind to calcium and inhibit either growth or aggregation of CaOx crystals. Only a few other proteins have been identified as inhibitors of stone formation [62][63][64].…”
Section: Proteomic Identification Of Novel Urinary Modulators Of Caoxmentioning
confidence: 99%
“…Interestingly, these stone inhibitors have similar physical and chemical properties; they are small anionic proteins that bind to calcium and inhibit either growth or aggregation of CaOx crystals. Only a few additional proteins have been identified as inhibitors of stone formation (27)(28)(29). In the present study, we have purified and identified a novel CaOx crystal growth inhibitor, namely urinary trefoil factor 1 (TFF1), from normal human urine using conventional biochemical methods and recent advances in mass spectrometry (MS).…”
Section: Introductionmentioning
confidence: 99%